Molecular assays for the diagnosis of sepsis in neonates: a diagnostic test accuracy review - Dierikx, Thomas H; Visser, Douwe H; de Meij, Tim; Versalovic, James; Leeflang, Mariska Mg; Cooper, Chris; Pammi, Mohan (Cochrane database of systematic reviews, 2025)
Microbial cultures for diagnosis of neonatal sepsis have low sensitivity and reporting delay. Advances in molecular microbiology have fostered new molecular assays that are rapid and may improve neonatal outcomes. To assess the diagnostic accuracy of various molecular methods for the diagnosis of culture-positive bacterial and fungal sepsis in neonates and to explore heterogeneity among studies by analyzing subgroups classified by gestational age and type of sepsis onset and compare molecular tests with one another. We searched CENTRAL, MEDLINE, Embase and trial registries in August 2023. We checked reference lists of included studies and systematic reviews where subject matter related to the intervention or population examined in this review. We included studies that were prospective or retrospective, cohort or cross-sectional design, which evaluated molecular assays (index test) in neonates with suspected sepsis in comparison with microbial cultures (reference standard). Two review authors independently screened studies, extracted data and assessed the methodological quality of the studies. We performed meta-analyses using the bivariate model and entered data into Review Manager. Seventy-four studies were eligible for inclusion, of which 68 studies provided data for meta-analysis. The total number of participants was 14,309 (1328 infants who were culture-positive and 12,981 infants who were culture-negative) from 68 studies that were included in the meta-analysis. The summary estimate of sensitivity was 0.91 (95% confidence interval (CI) 0.85 to 0.95) and of specificity was 0.88 (95% CI 0.83 to 0.92) (low-certainty evidence). We explored heterogeneity by subgroup analyses of type of test, gestational age, type of sepsis onset and prevalence of sepsis. We found insufficient explanations for the heterogeneity (low- to very low-certainty evidence). Sensitivity analyses including studies that analyzed blood samples, using good methodology and those that did not use multiple samples from the same participant revealed similar results (low-certainty evidence). Molecular assays have the advantage of producing rapid results and have moderate diagnostic accuracy. Molecular assays may prevent overuse of antibiotics in neonates with suspected sepsis. The efficacy and cost-effectiveness of these molecular assays should be evaluated using randomized trials comparing molecular assays as an add-on test versus conventional methods without the add-on test in neonates with suspected sepsis.